Angiorganoid: vitalizing the organoid with blood vessels. (12th September 2022) - Ma, Xiaojing; Li, Hongfei; Zhu, Shuntian; Hong, Zixuan; Kong, Weijing; Yuan, Qihang; Wu, Runlong; Pan, Zihang; Zhang, Jing; Chen, Yahong; Wang, Xi; Wang, Kai
Abstract : The emergence of the organoid simulates the native organs and this mini organ offers an excellent platform for probing multicellular interaction, disease modeling and drug discovery. Blood vessels constitute the instructive vascular niche which is indispensable for organ development, function and regeneration. Therefore, it is expected that the introduction of infiltrated blood vessels into the organoid might further pump vitality and credibility into the system. While the field is emerging and growing with new concepts and methodologies, this review aims at presenting various sources of vascular ingredients for constructing vascularized organoids and the paired methodology including de- and recellularization, bioprinting and microfluidics. Representative vascular organoids corresponding to specific tissues are also summarized and discussed to elaborate on the next generation of organoid development.